Business-government relations : concepts and issues - Colebatch, H. K.; Prasser, Scott; Nethercote, J. R. (South Melbourne : Nelson, 1997)
This book is divided into four parts: Analytical approaches; Arenas and participants; Alternative Explanations; and Conflict and change.
Keywords: Australia; Business; Politics; Australia -- Economic conditions; Australia -- Economic policy; Business and politics -- Australia; Industrial policy -- Australia